2006
DOI: 10.1177/1538192705282566
|View full text |Cite
|
Sign up to set email alerts
|

Models of Excellence in Multicultural Colleges and Universities

Abstract: The authors examine definitions of culture and philosophical and political assumptions that underlie multicultural approaches that facilitate or discourage multicultural competence. The authors discover that campus culture—determined mostly by the dominant coalition or power elite—is critical to success or failure of effective multi-cultural policies and procedures. In the literature, power is not generally acknowledged when considering multicultural competence. Thus, this preliminary work relating systems the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…These programs operate with the goal of providing resources and services specific to the needs of underrepresented students. Retention programs work to establish educational environments for students of color that facilitate a positive sense of self (Oseguera et al, 2009), assist students with a smooth transition into their freshmen year, and advocate for students of color (Lopez-Mulnix & Mulnix, 2006). Many of these programs, such as TRiO programs, summer bridge programs, and first-year retention programs, include elements that support students by building academic skills, providing cultural programming, tutoring, counseling, and peer mentoring (Lopez-Mulnix & Mulnix, 2006;Oseguera et al, 2009).…”
Section: Relevant Literaturementioning
confidence: 99%
“…These programs operate with the goal of providing resources and services specific to the needs of underrepresented students. Retention programs work to establish educational environments for students of color that facilitate a positive sense of self (Oseguera et al, 2009), assist students with a smooth transition into their freshmen year, and advocate for students of color (Lopez-Mulnix & Mulnix, 2006). Many of these programs, such as TRiO programs, summer bridge programs, and first-year retention programs, include elements that support students by building academic skills, providing cultural programming, tutoring, counseling, and peer mentoring (Lopez-Mulnix & Mulnix, 2006;Oseguera et al, 2009).…”
Section: Relevant Literaturementioning
confidence: 99%
“…In sum, proficient diversity leadership exhibits several characteristics (Alire, 2001;Jackson, 2006;Lopez-Mulnix and Mulnix, 2006;Mabokela and Madsen, 2003;Santiago, 1996;Sinclair, 2002Sinclair, , 2004Taylor, 1995):…”
Section: Practicing Diversity Leadershipmentioning
confidence: 97%
“…Higher education researchers found that Latino student attainment gaps were also related to students' experiences within adverse environments and stereotyping within institutions of higher education (Arbona & Nora, 2007;Hurtado & Ponjuan, 2005). They also found that a positive campus culture was a large determining factor in Latino degree attainment (López-Mulnix & Mulnix, 2006). In a longitudinal study of Latino students' perceptions of their undergraduate experiences Hurtado and Ponjuan (2005) found that students from Spanish-language dominant households were more likely to perceive hostile campus climates than those from English language-dominant households.…”
Section: Barriers To Attainmentmentioning
confidence: 99%